“Federação Mattogrossense pelo Progresso Feminino” : mulheres e emancipação nas três primeiras décadas do século XX em Cuiabá-MT - Gomes, Nailza da Costa Barbosa (2018)
The goal of this thesis is to investigate the quest for emancipation in Cuiabá-MT through associative activities that occurred in the first three decades of the 20th century with the creation of the outcome "Mattogrossense Federation For women's Progress" in the year of 1934. Matches that give visibility to the role of women, as well as mato-grossenses, your inclusion in the political debate of the period and especially highlight their presence in that scenario still invisibilizado by the sources and the speech historiographical sexist and Eurocentric. For both, the thesis had articles published in newspapers of the time, photographs, letters, official documents such as acts, rules and a significant participation of violet magazine. The theory, therefore, points to the operability of gender relations, patriarchy, representation, appropriation and emancipation, thus, find points of interest that make it possible to say that women here have made the difference in that society, though, conditioned by time and places.